Rancang Bangun Sistem Informasi Penjualan Jasa Percetakan Berbasis Website Studi Kasus : CV. Prima Framedia - Eka Puspita Sari; Eni Pudjiarti (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
CV. Prima Kreasi Framedia is a printing company located in East Jakarta. CV. Prima Kreasi Framedia started its operation in 2013. The main business of printing books, banners, brochures, and others is an affiliated company or not a group's subsidiary, but purely a company that operates independently. But the marketing system on the CV. Prima Kreasi Framedia is still not good enough. The way used in marketing the product is still using print media such as putting up banners and banners and even printing and distributing leaflets. For bookings and purchases, always can not be done online, requiring customers to come directly to the company to make booking and purchase transactions, the way is considered very inefficient. It takes an attractive website to market products and improves services and transactions more effectively and efficiently. The research method used consists of observation, interview, and literature study, while the system development model used is waterfall model, with PHP programming language and database used is MySQL. The result of this research is Website Based Printing Service Sales Information System. The website created can be used to source information about products and can also conduct transactions online efficiently.